Tokamak code TOKES: models and implementation - Landman, I.S. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
The code TOKES was recently developed aiming at integrated simulation of plasma equilibriums and surface processes in tokamaks. Main features of TOKES are described. The code calculates processes in multi-fluid plasma and neutral atoms in the vessel, including plasma heating by neutral beams, transport of hot plasma and electromagnetic radiation, and surface responses to the load, such as the sputtering and the vaporization. The magnetic field is also addressed. Недавно разработанный код ТОКЕС предназначен для объединенного моделирования плазменного равновесия в токамаке и процессов на поверхности стенки вакуумной камеры. Описаны основные свойства кода. ТОКЕС рассчитывает физические процессы в многожидкостной плазме и нейтральные атомы в камере, включая нагрев плазмы нейтральными пучками, перенос плазмы и электромагнитного излучения, а также реакцию стенки на нагрузку: атомное распыление и испарение. Магнитное поле также рассмотрено. Нещодавно розроблений код “ТОКЕС” призначений для об'єднаного моделювання плазмової рівноваги в токамаці і процесів на поверхні стінки вакуумної камери. Описано основні властивості коду. ТОКЕС розраховує фізичні процеси в багаторідинній плазмі і нейтральні атоми в камері, включаючи нагрів плазми нейтральними пучками, перенос плазми й електромагнітного випромінювання, а також реакцію стінки на навантаження: атомне розпилення і випар. Магнітне поле також розглянуто.